2015
DOI: 10.1093/heapol/czv034
|View full text |Cite
|
Sign up to set email alerts
|

Decentralization and decision space in the health sector: a case study from Karnataka, India

Abstract: Various attempts have been made in India with respect to decentralization, most significantly the 73rd Amendment to the Constitution of India (1993) which provided the necessary legal framework for decentralization to take place. However, the outcome has been mixed: an evaluation of the impact of decentralization in the health sector found virtually no change in health system performance and access to health services in terms of availability of health personnel or improvement in various health indicators, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 23 publications
1
30
0
Order By: Relevance
“…In Kenya, a country with a much younger history of devolution since 2013, one study described how devolution ironically decreased local level decision space and recommended transferring more autonomy to county hospitals [46]. Other studies likewise reported a preference to expand decentralization by increasing capacities in Tanzania [47] and India [17], and by widening local decision space further for human resources management in Ghana [48] and Uganda [13], and for several functions in Fiji [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Kenya, a country with a much younger history of devolution since 2013, one study described how devolution ironically decreased local level decision space and recommended transferring more autonomy to county hospitals [46]. Other studies likewise reported a preference to expand decentralization by increasing capacities in Tanzania [47] and India [17], and by widening local decision space further for human resources management in Ghana [48] and Uganda [13], and for several functions in Fiji [16].…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies, drawing from the decision space framework, have assessed the extent of autonomy enjoyed by local decision-makers in countries that have decentralized or devolved their health systems [12][13][14][15][16][17]. Most have attempted to come up with an overall or summative assessment of local decision space yet, in practice, decision-making for health services often involve multiple actors, each of whom may be wielding varying degrees of influence into the decision-making process.…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…Within the broader perspective, this indicates that since Nigeria is a UN member state, the influence of international health development goals like the GHI which prescribed how health funding, functioning and functionaries were to be achieved at the lower levels of government (Seshadri et al, 2016) is similarly felt in the country and in Yobe state. In fact, Nigeria's NSHDP adopted from the GHI like the health-related MDGs have emphasised reduction of child mortality, improvement in maternal health and efforts to combat communicable and non-communicable diseases by 2015 (Oyibocha et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…However, as policy makers and politicians are faced with numerous public health issues among other socio-economic challenges in Low and Middle-Income Countries (LMICs), how such decisions are made are often limited and challenging (Yang and Qian, 2016).To advance this key argument, we pose the question: what persuades policy makers to select certain public health priorities from competing for policy issues particularly in LMICs like Nigeria and Yobe state in particular? This is important as although there are various regional and national studies on HDA, the current literature simply ignored the roles of sub-national governments where in most cases such responsibilities lie with them (Seshadri et al;Umar and Bawa, 2016). Similarly, McCollum et al (2016) have argued that the while the global and national goals remain similar, the performance at sub-national national may depict different scenario with discrepancies that may bring about the potential for prioritisation in terms of goals in achieving health development in a particular place.…”
Section: Introductionmentioning
confidence: 99%
“…3 It has proven to be a useful framework to several other researchers, including most recently in Karnataka, India. 4 It is interesting to note that the approach does not seem to depend on the size of the country and that it can be applied to large states in India as well as to a small island country like Fiji. My approach also examines the relationship between "decision space" and the local capacities to exercise better choices.…”
mentioning
confidence: 99%